Critical Media Research, Globalisation Theory and Commercialisation - Ampuja, Marko (Javnost-The Public, 2004)
In this article, I will look at the status of critical research in contemporary analyses of the media. This kind of assessment should only be done keeping Fredric Jamesonís famous injunction in mind: always historicize! Critical communication scholarship is a historically evolving field of research which has, since its inception, responded to key social and theoretical developments, of which globalisation is the most significant recent example. After a brief historical overview of critical media research, I will concentrate in a more detailed way on the question of how critical perspectives relate to contemporary discussions of the media and globalisation (which are mutually constitutive). I will present several accounts of the relationship between media and globalisation and offer an analysis and criticism of these. The critical starting point for this essay is the fact that during the last couple of decades communication research and the development of media have largely followed their own separate paths. At a time when the media has become more and more commercialized throughout the world, the field of media studies has neglected critical economic considerations of the media. Therefore, the ire-introductionî of critical economical considerations of the media is a necessity. I conclude the paper by briefly examining the question of how critical media theory should position itself in light of the changes that the current wave of media commercialization and globalisation have brought about.